Analysis of mobile applications in use in Brazil for treatment of mental disorders - da Silva, Alciene Pereira; Lôbo, Rafaela Magalhães Manot Sarrat; de Magalhães , Júlia Barbosa; Santos, Roque Pinto da Silva; Honda, Marcelo Ossamu; Rosa, Darci de Oliveira Santa (Disciplinarum Scientia | Saúde, 2025)
This research sought to evaluate the available applications with free mental health content available in the two largest online stores in Brazil. This is an evaluative and descriptive study, which analyzed applications in the Apple Store® and Play Store® virtual stores. The results initially identified were 150 applications and, after applying the exclusion criteria, the sample was consolidated into 23 applications. It was concluded that the vast majority of programs analyzed were in non-compliance with Brazilian legislation, did not have a theoretical framework and were not fully aligned with the scientific content of mental health.